Strategi Pemasaran Melalui Aplikasi Motorku X pada Dealer Armada Tunas Jaya Motor Magelang dengan Pendekatan SWOT - Hesti Fitrianingsih; Andhatu Achsa (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2022)
The development of digital technology is increasing in today's modern era so that it has an impact on various aspects of life, especially in business. Armada Tunas Jaya Motor Magelang uses the Motorku X application as one of its marketing strategies. However, not all consumers use the Motorku X application so it is necessary to promote the Motorku X application to support their marketing strategy. The purpose of this research is to analyze the SWOT component of the Motorku X application to promote the application and to formulate alternative marketing strategies. This type of research is a qualitative descriptive study. Data analysis method in this research is SWOT analysis. The results of the SWOT matrix indicate that the alternative strategies that can be applied to the Armada Tunas Jaya Motor Magelang are the SO and WO strategies. The SO strategy is to increase the promotion of mobile marketing through personal selling and social media, to take advantage of the motorbike sales features available in the Motorku X application, to improve the quality of service both online and offline. The WO strategy is to require consumers to install the Motorku X application after purchasing a motorbike, increase promotion through sales promotion using the Motorku X application by providing discounts for purchasing special motorbikes at Tunas Jaya Motor Fleet and free service for a certain period of time, and providing attractive prizes or programs specifically for loyal consumers.